Outcomes of In-hospital Cardiac Arrest: Insights from a Medical Intensive Care Unit - Karthik Kailasam; Mahmoud Alwakeel; Xiaofeng Wang; Abhijit Duggal; Sudhir Krishnan (PLoS ONE, 2026)
Background Critically ill patients admitted to intensive care units (ICU) usually suffer from life-threatening illnesses, and many are hemodynamically unstable. The incidence of cardiac arrest in the ICU is approximately 22 per 1000 admissions, and survival to discharge after in-hospital cardiac arrest (IHCA) is approximately 14%. Variables associated with IHCA survival are poorly understood and the outcomes of cardiopulmonary resuscitation (CPR) in the ICU are poorly reported in the literature. We investigated the characteristics of IHCA and factors that are associated with poor IHCA survival. Methods and Findings After adjusting for age, APACHE III score, and initial rhythm, every one-minute increase in CPR duration was associated with 1.161 (95% CI 1.119–1.204; p < 0.0001) odds of death during resuscitation and 1.154 (95% CI 1.059–1.258; p < 0.0001) odds of death at the time of ICU discharge. Hospital survivors had a lower APACHE III score (Mean = 88.3, SD 29.8, IQR 66–106) and acute physiology score (Mean = 75, SD 30, IQR 56–94) compared to non-survivors. Hospital survivors were also more likely than non-survivors to have a shockable rhythm at the time of arrest (20% versus 7.5%), shorter average CPR duration (5.4 minutes versus 12.8 minutes), longer length of ICU stay (14 days versus 1.8 days) and longer length of hospital stay (25 days versus 6.1 days). Conclusion Based on our retrospective analysis, we conclude that the odds of IHCA mortality is directly proportional to the duration of CPR regardless of age, initial rhythm, and severity of underlying illness.